2020
DOI: 10.1609/aaai.v34i09.7085
|View full text |Cite
|
Sign up to set email alerts
|

On the Robustness of Face Recognition Algorithms Against Attacks and Bias

Abstract: Face recognition algorithms have demonstrated very high recognition performance, suggesting suitability for real world applications. Despite the enhanced accuracies, robustness of these algorithms against attacks and bias has been challenged. This paper summarizes different ways in which the robustness of a face recognition algorithm is challenged, which can severely affect its intended working. Different types of attacks such as physical presentation attacks, disguise/makeup, digital adversarial attacks, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“… Wang and Deng (2019) proposed a reinforcement learning-based race balance network (RL-RBN) to mitigate racial bias. Singh et al (2020) provided a review of techniques related to bias in face recognition.…”
Section: Related Workmentioning
confidence: 99%
“… Wang and Deng (2019) proposed a reinforcement learning-based race balance network (RL-RBN) to mitigate racial bias. Singh et al (2020) provided a review of techniques related to bias in face recognition.…”
Section: Related Workmentioning
confidence: 99%
“…Overall, existing works have demonstrated, beyond doubt, that “morphing” is a threat for face recognition systems. Several survey papers have also highlighted the vulnerability of face recognition algorithm against digital manipulation and limitations of existing detection algorithms ( Akhtar et al, 2019 ; Scherhag et al, 2019 ; Singh et al, 2020 ; Tolosana et al, 2020 ; Venkatesh et al, 2020 ). The survey papers bring out the boundaries of existing detection algorithms such as non-generalizability against manipulation types and image resolution and computationally inefficiency.…”
Section: Related Workmentioning
confidence: 99%
“…These systems have a growing effect on the daily life [78] and are increasingly involved in critical decisionmaking processes, such as in forensics and law enforcement. However, recent works [49], [4], [24], [53], [7], [25], [63] showed that current face recognition solutions possess biases leading to discriminatory performance differences [59] based on the user's demographics [67], [74].…”
Section: Introductionmentioning
confidence: 99%